Simulasi Model Sistem Kerja Pada Departemen Injection Untuk Meminimasi Waktu Work-In-Process - Riyanto, Ong Andre Wahyu (Universitas Muhammadiyah Surakarta, 2016)
The smooth process of manufacturing and production requires the operating machine in good condition. If the machine breakdown happened then the production process will be stopped, the production target was not achieved, due date can not be met. So that the costumer will become dissatisfied, and so on. The purpose of this study is to evaluate the work system of the injection department. Also reduce the waiting time for repair the broken machine at existing production system. This study propose the method of modeling and simulation for examine the working system object using the simulation software of Arena. Based on the experiment, it can be seen that the simulation model repair in scenario 1 give impact on the level of activity of technicians up to 20.2% without any reduction in processing time. From the simulation model, the scenario 2 giveÂ impact of changes in the levels of techniciansÂ activity decline by 5.56% and can decrease the processing time up to 8.33%.